Insights into Lewis/Brønsted acidity of metal chlorides and solvent effect of alcohols for synthesis of γ-valerolactone by combining molecular dynamics simulations and experiments. (1st March 2023) - Zhan, Qiwen; Lin, Qixuan; Liu, Yao; Ren, Junli; Li, Libo; Li, Weiying
Graphical abstract: Highlights: MD was used to observe the distribution of L/B acid around the reactants. ZrCl4 and HfCl4 achieved GVL yields of 61.88% and 68.13%. High IPL yields and high GVL yields were corresponded to different L/B acidity. The hypothesis that IPL was capable of H/D exchange was presented. Abstract: The synthesis of biofuel γ-valerolactone (GVL) from furfural is a multistep process that entails the regulation of Lewis/Brønsted (L/B) acidity of catalyst and the hydrogen donation ability of alcohols. In this study, experiments and molecular dynamics (MD) simulations were combined to get insights into the role of catalysts and solvents during the conversion of furfural to GVL. The capacities of various metal chlorides (divalent to hexavalent metal elements) and alcohols (primary and secondary alcohols) were comparatively investigated. The results showed that chlorides of Group IVB metals (ZrCl4 and HfCl4 ) exhibited excellent catalytic performance and achieved GVL yields of 61.88 % and 68.13 %, respectively. By preliminary statistical assessment, the intervals in which high isopropyl levulinate (IPL) yields and high GVL yields were found corresponded to different L/B acidity (3.5 < N < 4.8, −2 < Z < 1 and N < 5.7, Z > 1.5) (Z: Lewis acid strength. N: number of molecules in the shell). Secondary alcohols displayed the lower reduction potential but the higher interaction energy with reactants than that of primary alcohols. The distribution of Hf 4+ around the reactants was tendentious, whereas the distribution of C3 H7 OH 2+ was more homogeneous. The investigation of reaction mechanism proposed new understandings of the reacted sites of reactants and the hydrogen transfer of solvent to reactants. The hypothesis that IPL was capable of hydrogen/deuterium (H/D) exchange was developed.